An experimental investigation of interfacial instability in separated blood. Issue 4 (30th January 2019) - Wood, Ryan L.; Whitehead, Jared P.; Hunter, Alex K.; McClellan, Daniel S.; Pitt, William G.
Abstract : Experiments are done with separated human blood decelerated at constant rates to determine the maximum deceleration rate while avoiding remixing of the layers, which have different densities and viscosities. The deceleration rate affects both the stability and separation of particles through sedimentation. The velocity at onset of instability for a constant deceleration rate is experimentally determined for a 12‐cm‐diameter disk. Parameters of cell pack thickness, plasma thickness, and total thickness are investigated experimentally, and the only statistically significant parameter to affect stability is rate of deceleration. The data describe a correlation separating regions of stability and instability. To understand stability in decelerating flow of separated blood plasma and cells, the equations of motion are solved for a two‐layer fluid flow with a moving boundary and free surface. Inclusion of non‐Newtonian rheology of blood predicts large discontinuities in the shear rate, which is proposed as the cause of the interfacial instabilities. © 2019 American Institute of Chemical Engineers AIChE J, 65: 1376–1386, 2019